Pengelolaan Madrasah Sentralistik : Solusi atau Masalah? - Abd. Hamid Wahid (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2007)
In a reality, there is a gap between madrasah and school oh the quality achievement. It might be caused eitber by a high-load-curriculum in madrasah or the lack of government’s attention in service fulfillment. This condition brings upon some demands to bring back madrasah to the authority of department of national education (Depdiknas). Some perceive that madrasah are being marginalized under the autbority of department of religious affairs (Departemen Agama)- that its duty does not only bandle educationed problems. However, the department of religious affairs assures, the bringing back madrasah to depdiknas’ authority will be withering up most madrasahs- which generally are private madrasah- with its long history of  their existence. This paper will elaborate the madrasah’s management and its implementation.